Pembuatan Indeks Judul Tesis (S2) Beranotasi Program Studi Pendidikan Bahasa Indonesia Tahun 2005-2013 di Perpustakaan Pascasarjana Universitas Negeri Padang - Pernando, Syah Yuli; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of this paper is describing process and construction of thesis index (S2) annotated Indonesian Language Teaching study Program 2005-2013 in Undergraduate Program of Padang State University Library. Collecting the data was done by observation and directly participation by collecting data from authentic source. Data analysis is descriptive method. The process of construction this thesis index annotated was started by examining thesis information that will be indexed, and then selected, grouped, noted the data, created the annotation, determined the key words, created the thesis index, and typed the index. The thesis that had indexed were been 197 titles. Keywords: index anotation; indexing; thesis